Midlife Intakes of the Isoflavone Genistein and Soy and the Risk of Late-life Cognitive Impairment: The JPHC Saku Mental Health Study - Thomas Svensson; Norie Sawada; Masaru Mimura; Shoko Nozaki; Ryo Shikimoto; Shoichiro Tsugane (Journal of Epidemiology, 2023)
Background: The number of people with cognitive impairment, including dementia, in the world is steadily increasing. Although the consumption of isoflavones and soy is associated with a reduced risk of cardiovascular disease, it might also be associated with cognitive impairment. The low number of studies investigating the association between soy/isoflavone intake and cognitive function warrant additional research. Methods: The Japan Public Health Center-based prospective (JPHC) Study is a large population-based cohort. Midlife dietary intake of soy and the isoflavone genistein was assessed on two occasions: in the years 1995 and 2000. In 2014–2015, 1,299 participants from Nagano prefecture completed a mental health screening. Of these, a total of 1,036 participants were included in analyses. Logistic regression was used to determine Odds Ratios (OR) and 95% Confidence Intervals (CI) for the association between midlife energy-adjusted genistein and soy food intake and cognitive impairment. Results: There were 392 cases of cognitive impairment (346 cases of MCI and 46 cases of dementia). Compared to the lowest dietary quartile of energy-adjusted genistein intake, the highest quartile was significantly associated with cognitive impairment (OR = 1.51; 95% CI, 1.02–2.24; P for trend = 0.03) in the final multivariable analysis. Conclusion: High midlife intake of the isoflavone genistein is associated with late-life cognitive impairment.